PENGARUH EFIKASI DIRI DAN PENDIDIKAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA PENDIDIKAN TATA NIAGA FAKULTAS EKONOMI UNIVERSITAS NEGERI MALANG TAHUN 2013 - Zulianto, Mukhamad; Santoso, Sigit; Sawiji, Hery (Jurnal Pendidikan Insan Mandiri, 2015)
The purpose of this study was to determine: (1) Whether there is any influence of self-efficacy on student interest in entrepreneurship Commerce Education Program Faculty, State University of Malang, (2) Whether there is influence of entrepreneurship education on student interest in entrepreneurship Commerce Education Program Faculty, State University of Malang, and (3) Whether there is any influence of self-efficacy and entrepreneurial education together toward student interest in entrepreneurship Commerce Education Program Faculty, State University of Malang.This research is a descriptive study with a comparative approach. The population was students Prodi Commerce Education FE UM in 2013 as many as 153 students. The study sample of 61 students of department of Commerce Education FE UM has administer entrepreneurship education, taken proportionate stratified random sampling technique. The data collection technique used was a questionnaire method. Data analysis techniques performed by multiple linear regression.The results of this study are as follows: (1) The results of the t test showed that the significant value of t is 0.044. This value is smaller than 0.05. The first hypothesis states that there is a significant effect of self-efficacy on student interest in entrepreneurship proved significant. (2) The results of the t test showed that the significant value of t is 0.697. The second hypothesis states that there is a significant influence of entrepreneurship education on student interest in entrepreneurship proven positive effec, but not significant at 0.05. (3) that the F test significance value of t is 0.088. The third hypothesis states that there is a significant effect of self-efficacy and entrepreneurial education together proved to be a positive influence, but not significant at 0.05.Keywords: Entrepreneurship Education, Theory of Planned Behavior, Entrepreneurial Intention